2009
DOI: 10.5194/angeo-27-3551-2009
|View full text |Cite
|
Sign up to set email alerts
|

Solar off-limb line widths with SUMER: revised value of the non-thermal velocity and new results

Abstract: Abstract. Alfvén waves and ion-cyclotron absorption of high-frequency waves are frequently brought into models devoted to coronal heating and fast solar-wind acceleration. Signatures of ion-cyclotron resonance have already been observed in situ in the solar wind and in the upper corona. In the lower corona, one can use the line profiles to infer the ion temperatures. But the value of the so-called "non-thermal" (or "unresolved") velocity, potentially related to the amplitude of Alfvén waves propagating in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
4
0
0
Order By: Relevance
“…Moreover, Dolla & Solomon (2008) reported detection of Alfvén waves from the study of the variation of line widths in coronal hole off-limb region by analyzing SUMER/SOHO data, but they claim no evidence for damping of the Alfvén waves because they found that the effect of stray light explained the observed decrease with height in the width of several spectral lines, starting about 0.1-0.2 R ⊙ above the limb. This result was also confirmed from a later study by Dolla & Solomon (2009).…”
Section: Introductionsupporting
confidence: 83%
“…Moreover, Dolla & Solomon (2008) reported detection of Alfvén waves from the study of the variation of line widths in coronal hole off-limb region by analyzing SUMER/SOHO data, but they claim no evidence for damping of the Alfvén waves because they found that the effect of stray light explained the observed decrease with height in the width of several spectral lines, starting about 0.1-0.2 R ⊙ above the limb. This result was also confirmed from a later study by Dolla & Solomon (2009).…”
Section: Introductionsupporting
confidence: 83%
“…The present paper, however, do not consider the role of ion-cyclotron heating and assumes that all ions have a common temperature at a given height. Perhaps, it is worthwhile to note that the temperature derived in this paper is in line with that of the ions with high chargeto-mass ratio obtained by Dolla and Solomon (2009, their Figure 5). The derived non-thermal velocities at heights of 57 ′′ and 102 ′′ are also equal within the error bars in both papers.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…According to the study by Dolla and Solomon (2008), it was found that the temperature of Fe X is particularly larger than others. A similar result was also obtained by the authors for Fe VIII in the following paper (Dolla and Solomon 2009). The authors suggested that this result constitutes a clue to ion-cyclotron heating, since the study of ion-cyclotron heating shows that the ions with the lowest charge-to-mass ratios always absorb a major portion of the wave energy and leave nothing to appreciably heat the other ions (e.g., Vocks and Marsch 2002).…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 1 more Smart Citation